Agricultural Entrepreneurs and Colonist Farmers: Colonization and Agrarian Conflict in the Antioquia Border (1926-1947) [Entrepreneurs Agricoles Et Paysans Colons: Colonisation Et Conflit Agraire À la Frontière de L Antioquia (1926-1947)] [Empresários Agrícolas E Colonos Camponeses: Colonização E Conflito Agrícola Na Fronteira Antioqueña (1926-1947)] [Empresarios Agrícolas y Campesinos Colonos: Colonización y Conflicto Agrario en la Frontera Antioqueña (1926-1947)] - Henao-Holguin, D (Sello editorial Universidad del Atlantico, 2021)
This article analyses the conflicts between agricultural entrepreneurs and colonist farmers within the colonization context towards the region of Magdalena Medio in Antioquia. These conflicts are studied in the farmer protests cycle from 1926 to 1947. This period was characterized by the use of the legal apparatus by those actors who occupied the border. Nevertheless, there were also expressions of violence seeking to prevent the distribution of the land. Contentiousness in this area is dynamic because it arises not only from top to bottom, but also in horizontally among all sectors involved. © 2021 Sello editorial Universidad del Atlantico. All rights reserved.
Keywords: Agrarian border; Agrarian conflict; Agricultural entrepreneurs; Colonists farmers; Violence